Sosialisasi Dampak Pernikahan Dini Dari Perspektif Agama Dan Kesehatan di Desa Mekar Sari Kecamatan Suela Kabupaten Lombok Timur - Muhamad Akrom; Ahmad Wibi Irsyadillah; Muhammad Hafizin; Mashal Hadi (BALE LITERASI, 2022)
Child marriage or early marriage is still a serious problem in Indonesia. School students as the generation in this age group need to have comprehensive knowledge regarding the causes and consequences of child death as a preventive measure. This socialization activity is important to do with the aim of changing students' perceptions of the causes and effects of child marriage or early marriage. This service activity was carried out using the socialization method and took place at Maraqitta'limat Mekar Sari Islamic High School. As many as 40 participants from class XII and their parents took part in the activity. After socialization, their perception, and understanding of early changes. They believe early marriage will bring losses in terms of psychological, biological, and aspects of social life. This shows that after the socialization was held, students' perceptions and understanding changed.